Effective meeting in graduate research student supervision - Zainal Abiddin, Norhasni; West, Mel (Science Publications, 2007)
Meeting with supervisor is part of the practices for any graduate research students. However, was the meeting effectively conducted? Did the meeting really helped the student to progress in their research and did the supervisor given proper guidance and advices to the student during the meeting? This article focuses on the practices on supervision especially the effective methods of conducting meeting from twelve PhD students studied at Manchester, United Kingdom of three major disciplines of study namely Arts, Science and Social Sciences. It reviewed the major findings of the research through in-depth interviews. The results had shown that in order to progress well in their research, they must no doubt be involved in more regular meetings or discussions process and to go through certain levels before, during and after each meeting. Those levels are very important to be implemented in order to ensure that the meetings with the supervisor have great implication to the research students. It should be practiced by lecturers, students and especially the foreign students in order to optimise the effectiveness of the meeting and relationship between student and supervisor.